Influence of conductive fillers on the mechanical and thermal performance of stone mastic asphalt (SMA) mixtures - Moinul Hossain; Mujib Rahman; Denis Chamberlain; Tala Kasim (Case Studies in Construction Materials)
This paper examines the thermal and mechanical properties of asphalt mixtures incorporating conductive fillers such as graphene, graphite, and magnetite. In terms of mechanical properties, conductive mixtures showed improved compaction with lower voids content at the same compaction temperature and effort. The stiffness values of all conductive mixtures were approximately 40 %–60 % higher than those of the control mix, potentially better load spreading ability. Thermal conductivity was assessed at three test temperatures (5°C, 25°C, and 40°C) under both virgin and aged conditions. The highest thermal conductivity was observed at 25°C, where a mixture containing 3 % graphene, 10 % graphite, 10 % magnetite, and 10 % limestone demonstrated an 84.08 % increase in thermal conductivity compared to the control mixture with limestone filler. Furthermore, while thermal conductivity decreased with ageing across all mixes and test temperatures, conductive mixtures still exhibited 15 %–20 % higher thermal performance than the control mixture. These findings suggest that conductive fillers help to mitigate oxidative ageing, thereby enhancing long-term resistance to cracking. In terms of durability, all conductive mixtures demonstrated superior ageing and moisture resistance, retaining stiffness values 10 %-20 % higher than the control mixture after long-term ageing and moisture conditioning cycles 5 %–20 % more stiffness compared to control mixture. These results are promising and indicate that incorporating cost-effective conductive fillers can not only enhance thermal performance leading to improved self-healing characteristics but also improve mechanical properties.